2020
DOI: 10.1002/er.5436
|View full text |Cite
|
Sign up to set email alerts
|

Photo‐thermal conversion and heat storage characteristics of multi‐walled carbon nanotubes dispersed magnetic phase change microcapsules slurry

Abstract: Summary The development of high‐efficient working fluids with excellent photo‐thermal conversion and heat storage properties is an important factor to solar thermal utilization. In this work, magnetic phase change microcapsules (MPCMs) were prepared via in situ polymerization, where melamine‐formaldehyde (MF) resin and octadecane containing oleic acid‐coated magnetic nanoparticles (OA‐MNs) were used as the shell and core, respectively. The microstructure, magnetic and thermal properties of MPCMs were investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…This can be explained by the high irradiation intensity leading to a shorter time to charge the sample, which may cause less energy loss. Furthermore, Table presents the photothermal conversion and storage capacity of other research on octadecane-based phase change composites. , Table S4 also compares various other organic PCMs serving as the primary component of a range of composites, illustrating a comprehensive picture of the innovative nature of the research. The results of this study, in comparison to those reported in the existing literature, position the work at a relatively high level. These findings affirm the exceptional photothermal conversion and storage capacities of the composite PCMs synthesized in this work.…”
Section: Resultsmentioning
confidence: 77%
“…This can be explained by the high irradiation intensity leading to a shorter time to charge the sample, which may cause less energy loss. Furthermore, Table presents the photothermal conversion and storage capacity of other research on octadecane-based phase change composites. , Table S4 also compares various other organic PCMs serving as the primary component of a range of composites, illustrating a comprehensive picture of the innovative nature of the research. The results of this study, in comparison to those reported in the existing literature, position the work at a relatively high level. These findings affirm the exceptional photothermal conversion and storage capacities of the composite PCMs synthesized in this work.…”
Section: Resultsmentioning
confidence: 77%
“…Carbon nanotubes (CNTs) are widely used in seawater desalination [ 1 , 2 , 3 , 4 , 5 , 6 ], environmental protection [ 7 ], thermal energy storage [ 8 , 9 , 10 , 11 ], photothermal dynamic therapy [ 12 , 13 , 14 ], and photodetectors [ 15 , 16 , 17 , 18 ] because of their efficient photothermal conversion ability. However, the synthesis process of CNTs is difficult to control strictly, which often induces complex morphologies and chirality distribution; simultaneously, some defects and impurities are also introduced.…”
Section: Introductionmentioning
confidence: 99%
“…Microencapsulated phase change materials (MicroPCMs) have expanded the application and market prospects of phase change materials [ 1 , 2 , 3 , 4 ], which include textiles, dyeing and printing [ 5 , 6 , 7 ], building energy saving [ 8 , 9 , 10 ], microencapsulated phase change slurry [ 11 , 12 , 13 ] and composite foam [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%